Role of age in management of clubfoot by ponseti method and relapse rate - M.S. Patil; Md. Nayeem Ali; Renuka M. Patil (Al Ameen Medical College, 2014)
Background: With all the stirring advances in modern medicine, it is somewhat sobering to assess the fund of knowledge concerning the treatment of clubfoot. Evolution of treatment started with manipulation, strapping etc.; with not much enthusiastic results. Surgical intervention came into scene; with not much success and lasting morbidity. Over the past decade, Ponseti management has become accepted throughout the world, as the most effective and least expensive treatment of clubfoot.Does the age at beginning of treatment has influence,in Ponseti method and rate of relapse is uncertain. Aims and objectives: (1) Role of age at beginning of treatment. (2)Relapse rate. Materials and method: 58 patients were enlisted for study with 96 idiopathic club feet treated by Ponseti method at Al Ameen Medical College Hospital and its ancillary branches between 2006-2012; with minimum follow up of 30 months. Two groups were made, group I with age ≤6 months of age and group II with age >6 months. Results: Average number of casts necessary to achieve correction in group I was 5.28 casts (range 4 to 8 casts); while in group II was 7.31 (range 6- 11 casts). Percutaneous tenotomy was needed in 85.42% of feet. Relapse rate was 7.14% (5 feet) in group I while 15.3% (4 feet) in group II. Conclusion: Effectiveness of Ponseti technique in achieving the correction of deformity and functional as outcome increases with early age of initiation of treatment while relapse rate increases with increase in age.